A critical survey of empirical methods for evaluating active labor market policies - Jeffrey Smith (The University of Western Ontario, Department of Economics, 2000)
[Conclusions] This paper has reviewed and commented on recent developments in evaluation research. I have outlined recent methodological developments and their implications for evaluation practice and policy. I have also provided copious citations to the technical literature related to these developments. My main conclusion is that while much has been learned over the past three decades, there remains a lot of room for improvement in econometric evaluation methodology and, even more so, in evaluation practice.
Keywords: 330; Arbeitsmarktpolitik; Kritik; Theorie